PENGARUH CUSTOMER RELATIONSHIP MARKETING TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN SERVICE CENTER PT MULTI AUTO INTRAWAHANA DI KOTA PEKANBARU - Musisko, Dede; Jushermi, Jushermi; Wasnury, Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was conducted at PT. Multi Auto Intrawahana Pekanbaru. The purpose of this study was to determine the effect of Customer Relationship Marketing on Customer Satisfaction and Customer Loyalty Service Center PT Multi Auto Intrawahana in Pekanbaru. The population in this study is the customer service at PT. Multi Auto Intrawahana in Pekanbaru, amounting to 2486 people and the determination of the sample in this study using a formula Slovin and taken to the sampling method accidental sampling. Number of samples of this study are 96 customer service cars mazda in the previous year. The results of the study data analysis method using path analysis through IBM SPSS Version 20.0 shows that: 1) There is the influence of Customer Relationship Marketing on Customer Satisfaction Service Center PT. Multi Auto Intrawahana in Pekanbaru. 2) There is the influence of Customer Relationship Marketing on Customer Loyalty Service Center PT. Multi Auto Intrawahana in Pekanbaru. 3) influences of Customer Satisfaction to Customer Loyalty Service Center PT Multi Auto Intrawahana in Pekanbaru. 4) There is the influence of Customer Relationship Marketing on Customer Loyalty through Customer Satisfaction Service Center PT. Multi Auto Intrawahana in Pekanbaru.Keywords : Customer Relationship Marketing, Customer Satisfaction, Customer Loyalty